Targeting transforming growth factor-β1 by methylseleninic acid/seleno-L-methionine in clear cell renal cell carcinoma: Mechanisms and therapeutic potential - Aseel O. Rataan; Yan Xu; Sean M. Geary; Yousef Zakharia; Eman S. Kamel; Youcef M. Rustum; Aliasger K. Salem (Cancer Treatment and Research Communications)
Clear cell renal cell carcinoma (ccRCC) poses a significant global health challenge as its incidence continues to rise, resulting in a substantial annual mortality rate. Major clinical challenges to current ccRCC treatments include high drug-resistance rates as well as dose-limiting adverse events; underlining the need to identify additional ‘druggable’ targets. TGF-β1, VEGF, and PD-L1 are potential therapeutic targets in ccRCC. This study analyzed their expression in human ccRCC cell lines and patient tumor biopsies. Data obtained from western blotting demonstrated higher levels of TGF-β1 and PD-L1 and lower levels of VEGF in sarcomatoid ccRCC cell lines compared to non-sarcomatoid ccRCC cell lines. In patient samples, TGF-β1 was significantly upregulated in both non-sarcomatoid and sarcomatoid ccRCC tumors. It was demonstrated through two assays (cellular thermal shift assay and a size exclusion assay) that methylseleninic acid (MSA) binds specifically and directly to TGF-β1. MSA treatment significantly downregulated TGF-β1, PD-L1, and VEGF in a dose- and time-dependent manner in both non-sarcomatoid and sarcomatoid ccRCC cell lines. Seleno-L-methionine (SLM) treatment in a nude mouse xenograft model showed a significant tumor growth inhibition and TGF-β1 downregulation at non-toxic doses. These findings suggest that selenium-mediated downregulation of TGF-β1, PD-L1, and VEGF could be a viable therapeutic strategy for ccRCC.